2016
DOI: 10.1038/srep37586
|View full text |Cite
|
Sign up to set email alerts
|

Discerning the Location and Nature of Coke Deposition from Surface to Bulk of Spent Zeolite Catalysts

Abstract: The formation of carbonaceous deposits (coke) in zeolite pores during catalysis leads to temporary deactivation of catalyst, necessitating regeneration steps, affecting throughput, and resulting in partial permanent loss of catalytic efficiency. Yet, even to date, the coke molecule distribution is quite challenging to study with high spatial resolution from surface to bulk of the catalyst particles at a single particle level. To address this challenge we investigated the coke molecules in HZSM-5 catalyst after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Of note is the pioneering work contributed by Weckhuysen et al that provides critical insights into coking and deactivation. With the help of two advanced microscopic techniques: confocal fluorescence microscopy (CFM) 10,15 and atom probe tomography (APT) [16][17][18] , they visualized the spatial distribution of coke deposits at sub-µm or sub-nm scale in a single catalyst particle, and identified the affinity between the acid sites (enriching on the nearsurface region of catalysts) and the coke clusters (located in the same region) 16,17 . These microscopic techniques can unprecedentedly provide effective information on the spatial distribution of coke molecules.…”
mentioning
confidence: 99%
“…Of note is the pioneering work contributed by Weckhuysen et al that provides critical insights into coking and deactivation. With the help of two advanced microscopic techniques: confocal fluorescence microscopy (CFM) 10,15 and atom probe tomography (APT) [16][17][18] , they visualized the spatial distribution of coke deposits at sub-µm or sub-nm scale in a single catalyst particle, and identified the affinity between the acid sites (enriching on the nearsurface region of catalysts) and the coke clusters (located in the same region) 16,17 . These microscopic techniques can unprecedentedly provide effective information on the spatial distribution of coke molecules.…”
mentioning
confidence: 99%
“…Edmondson et al 19 studied nanosized bubbles in ferritic alloys using APT and found that the bubbles could be visualized using iso-density surfaces at approximately half the atomic density of the alloy, indicating bubbles were shown as lowdensity regions. Porous zeolite catalysts were recently investigated using APT by two independent research teams [22][23][24][25] . Although pores have zero atomic density inside, i.e., empty space, no such regions were found in the APT reconstructions 23 .…”
mentioning
confidence: 99%
“…Porous zeolite catalysts were recently investigated using APT by two independent research teams [22][23][24][25] . Although pores have zero atomic density inside, i.e., empty space, no such regions were found in the APT reconstructions 23 . Rather, spatial correlations of regions with high densities and high concentrations of segregated elements in the proximity of the pores suggest that pores may present as high-density regions in the 3D reconstruction.…”
mentioning
confidence: 99%
“…Using SAPO-34 instead of H-ZSM-5 catalysts also showed that coke formation during the methanol-to-hydrocarbons reaction correlates with the presence of acid sites, with differences in the cluster number, cluster size, and number of coke-depleted regions between the two catalysts [194]. Similar experiments were performed regarding the ethanol-to-hydrocarbon reaction [195] run for a longer time (72 h) to assess the industrial relevance of the analysis. Similarly to [191], a non-uniform distribution of Al and the formation of C-rich region can be observed after reaction, showing the usefulness of the APT methodology to study the coke formation in zeolites.…”
Section: Catalysts As Porous Materials-zeolitesmentioning
confidence: 75%